HUKUM PENERAPAN PRINSIP TRANSPARANSI DALAM PENGELOLAAN DANA ZAKAT - Muharir Muharir; Solihah Sari Rahayu (Prodi Hukum Ekonomi Syariah (Muamalah), 2018)
This study tried to analyze the application oftransparency principle in the management of Zakat funds at the Amil Zakat Institute ofZakat Center people Panumbangan Unit. The purpose of this research to know theapplication of the principle of transparency in the management of Zakat funds in the AmilZakat Institute of Zakat Center people Panumbangan Unit. The methods used aredescriptive analysis, while data collection is done with interviews, observations anddocument studies and library data. The results of this research is openness and ease inobtaining information about the management of zakat funds in the Amil Zakat Institute ofZakat Center people Panumbangan Unit can only be accessed through monthly reports inthe form of newsletters and Facebook. This is due to lack of capital and human resourcesin the institution of Amil Zakat Central Zakat people unit Panumbangan less. Applicationof the principle of transparency in the management of Zakat funds in the Amil ZakatInstitute of Zakat Center people Panumbangan Unit is not optimal, because access to information is still limited that only through monthly reports in the form of newslettersand Facebook